2020
DOI: 10.1111/jerd.12617
|View full text |Cite
|
Sign up to set email alerts
|

Over‐the‐counter bleaching agents can help with tooth whitening maintenance

Abstract: Objective This study evaluated the influence of over‐the‐counter agents on the maintenance of color and microhardness of the enamel after home bleaching protocol. Materials and methods Specimens of bovine teeth (6 × 6 × 2 mm) were prepared, and color (Easyshade, VITA) and microhardness (HMV‐2, Shimadzu) readings were performed. All the specimens were bleached using 22% carbamide peroxide (22%CP), except for the control group, and then separated into seven groups (n = 10) according to the interaction of toothpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
(50 reference statements)
1
14
0
3
Order By: Relevance
“…Moreover, ΔE1 and ΔE2 mean values of Coconut Oil Swish (study group) recorded 1.24 and 2.23 respectively; which are not perceptible clinically as the difference is clinically perceptible only when ΔE values are over 3.46 units (30) . This result is consistent with a study of Karadas & Hatipoglu, 2015 (9) and Olivia, 2020 (31) , found that whiteness of teeth treated with different hydrogen peroxide and carbamide peroxide containing mouthwashes increased over time and that it was significantly higher than the whiteness of teeth that received no treatment. Moreover, Crest 3D White mouth-rinse recorded the highest recovery whitening efficacy between a group of whitening toothpastes and mouth-rinse products, this study was done on bleached teeth stained in coffee solution (32) .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, ΔE1 and ΔE2 mean values of Coconut Oil Swish (study group) recorded 1.24 and 2.23 respectively; which are not perceptible clinically as the difference is clinically perceptible only when ΔE values are over 3.46 units (30) . This result is consistent with a study of Karadas & Hatipoglu, 2015 (9) and Olivia, 2020 (31) , found that whiteness of teeth treated with different hydrogen peroxide and carbamide peroxide containing mouthwashes increased over time and that it was significantly higher than the whiteness of teeth that received no treatment. Moreover, Crest 3D White mouth-rinse recorded the highest recovery whitening efficacy between a group of whitening toothpastes and mouth-rinse products, this study was done on bleached teeth stained in coffee solution (32) .…”
Section: Discussionsupporting
confidence: 92%
“…The search of clearer teeth has been constant, as the beauty and harmony of the smile is often linked with the color of the teeth. 1 Thus, tooth whitening has become the most popular esthetic treatment in dentistry due to being a conservative approach [2][3][4] and the color of teeth has been one of the most determinant factors for patients' satisfaction and self-esteem. 5 Tooth whitening can be performed by different techniques (inoffice and/or at home) and regardless of the whitening technique used, hydrogen peroxide is the agent responsible for the whitening effect.…”
Section: Introductionmentioning
confidence: 99%
“…Mouth rinses are adjunct over-the-counter substances for mouth cleansing. Whitening mouth rinses supposedly present a tooth whitening effect, mainly produced by substances such as hydrogen peroxide 5,21 . Considering the acquisition of mouth rinses does not require a professional prescription, anybody can use them, including individuals with esthetic dental restorations.…”
Section: Discussionmentioning
confidence: 99%